DEVELOPMENT OF MACROMEDIA FLASH-BASED LEARNING MEDIA IN SIMPLE MACHINES FOR CLASS VIII - Anggraeni, Fitri; Nur Hayati (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2025)
The role of learning media in the learning process is very important because it can foster student interest and activeness. One of the media that can be used in the learning process is macromedia flash-based learning media. Macromedia flash media can combine images, writing and sound. This research and development aims to determine the feasibility of the product based on the validity, practicality and effectiveness of macromedia flash-based learning media on simple aircraft material. This research was developed using the ADDIE development model which consists of 5 stages. The instruments used are validation sheets to determine the suitability of the media, student response questionnaires to determine the practicality and post test questions to determine the effectiveness of the media. The data obtained is qualitative data in the form of input and suggestions from validators and quantitative data in the form of assessment scores obtained from validation sheets of validation assessment results from media experts, material experts and practitioners, practicality data obtained from the results of student response questionnaires and data obtained from the completeness of learning outcomes. students in the form of a post test. Based on the research results, it is known that; 1) The validation result score was 90.7% with very valid criteria 2) The student response questionnaire score was 97% with very practical criteria 3) The post test score was 80% with effective criteria